PERUBAHAN SOSIAL BUDAYA DAN INTERAKSI SOSIAL MASYARAKAT GAMPONG BALEE KABUPATEN ACEH BARAT - Angriani, Dessy; Firza, Mitra; ndruru, Tomi; Nasution, Susi; wahyuniati, Wahyuniati (Universitas Teuku Umar, 2025)
Changes in values, norms, and culture have an impact on society's social relations, including changes in interactions that occur in society due to shifts in values, norms, and culture that occur. The change in values and norms in Bale Gampong society cannot be denied, this is caused by several factors such as a lack of understanding of religious values, social control of society, and the rapid development of technological advances. This research uses a qualitative method with a descriptive approach. Determining informants is a form of determining informants using purposive sampling. The theory used is the symbolic interactionalism theory of Herbert Mead. The research results show that every change greatly influences people's social interactions. Many interactions are affected and have an impact on the relationships that exist between individuals and individuals, individuals and groups, and groups and groups. Changes in values, norms, and culture in the Gampong Bale community include a culture of cooperation, sources of income that can no longer be used in the livelihood process, and several other changes that are occurring now are a form of change in community interaction which ultimately reduces community solidarity.